Is it me or others who matter? The interplay between consumer values vis-à-vis status and affiliation motives as shapers of meat alternative interest - Pennanen, Kyösti; Malila, Roosa-Maaria; Luomala, Harri T. (Elsevier, 2023)
This study is about the role of consumers' personal values (Self-enhancement, Openness to change, Self-transcendence, and Conservation) in consumers' interest towards meat alternatives. In addition, the underlying role of two social motives, status and group affiliation are analysed. A conceptual model with hypotheses was developed and validated, and the hypotheses were tested through PLS-SEM with data from four European countries (Finland, the UK, Germany, and Sweden, total N = 3600). The results show that self-focused personal values (Self-enhancement and Openness to change) are not associated with consumers’ interest towards meat alternatives. The case is different with other-focused values. Self-transcendence had a positive connection to interest while Conservation had a negative relationship. Finally, the data suggest an underlying role of social motive status between Self-enhancement and interest and the same for group affiliation between Self-transcendence and Conservation and interest. Based on the results, strategies to support meat alternative adoption such as value activation through priming, cognition and emotion-driven marketing are proposed.
Keywords: Meat alternatives; Personal values; Status; Group affiliation; PLS-SEM; fi=Markkinointi|en=Marketing|